HGH, EPO, anabolic steroids and testosterone in swimming - Rushall, B. S.; Grant, G. (Australian Swimming and Fitness, 1998)
This article briefly covers human growth hormone (hGH), erythropoietin (EPO), and androgenic anabolic steroids and testosterone, and their potential for improving swimming performances. Knowing the potential of these particular substances (hereafter called "drugs") will allow swimmers, parents, coaches, and officials to more effectively monitor swimmers' behaviors for signs of this destructive practice.